Cleavage speed and implantation potential of early-cleavage embryos in IVF or ICSI cycles - Lee, Meng-Ju (Springer US, 2012)
We examined whether there is a correlation among early embryo cleavage, speed of cleavage, and implantation potential for in-vitro fertilization (IVF) treatment and intracytoplasmic sperm injection (ICSI). This retrospective study examined 112 cycles of IVF and 82 cycles of ICSI in patients less than 40 years of age. Early cleavage was defined as embryonic mitosis occurring 25–27 h after insemination. These day-3 embryos were then grouped according to cleavage speed (rapid, normal, and slow) and morphological quality (good or poor). A larger proportion of early-cleavage embryos developed normally compared to non-early-cleavage embryos (IVF: 69.1 % vs. 47.1 %, respectively; ICSI: 63.0 % vs. 45.6 %, respectively). The early-cleavage embryos also produced more good quality embryos than the non-early-cleavage embryos (IVF: 80.2 % vs. 56.4 %, respectively; ICSI: 73.4 % vs. 59.4 %). The implantation rate was significantly higher with early-cleavage embryos in both IVF (42.9 % vs. 19.7 %) and ICSI (48.1 % vs. 24 %). These results indicate that early-cleavage embryos have a higher rate of normal development and develop into better quality embryos on day 3, resulting in more and higher quality embryos to choose from for day-3 embryo transfer. Thus, early cleavage may be a useful criterion when selecting embryos for IVF or ICSI.